Assessment of Opportunities for developing ecotourism in Kamalpokhari watershed area, Pokhara, Nepal (Janapriya Journal of Interdisciplinary Studies, 2025)
This study was conducted to assess the opportunities for developing ecotourism in Kamalpokhari, Pokhara valley, Nepal. Primary data was collected using a Household Survey (N=116), Focus Group Discussions (N=2), Key Informants Interviews (N=10), and Direct Field Observations. Secondary data was collected via a literature review. Data were analyzed using descriptive statistics. Perceptions of the local people were assessed using three points Likert scale and a Chi-square test was employed to assess the variation in their perception. Friedman’s test was used to assess the priority given by them among the existing products. Our study showed that local people ranked religious sites as the most attractive product followed by the lake and scenic beauty, Kahun Hill and lastly hiking in existing ecotourism products. Picnic spots, botanical gardens, bird watching, fish farming, and boating can enhance further opportunities for ecotourism development. The majority of the people were found to be positive towards the ecotourism development. However, ecotourism opportunities vary within the level of literacy rate of community people. Cleanliness programs, plantation, awareness programs, eco-club formation, and conservation programs were management activities adopted for conserv biodiversity. Thus, identification of ecotourism products and managing biodiversity played a significant role in the development of ecotourism.